A case report of absolute thrombocytopenia with ticagrelor. Issue 4 (6th July 2020) - Khan, Mahin R; Adhikari, Govinda; Khan, Hafiz; Changezi, Hameem U
Abstract: Background: We report a rare case of absolute thrombocytopenia with ticagrelor after 6 h of single loading dose of ticagrelor. Case summary: A 68-year-old male with ischaemic cardiomyopathy, hypertension, and dyslipidaemia presented with chest pain. He was found to be in new-onset atrial flutter and ruled in for a non-ST-segment elevation myocardial infarction. An echocardiogram showed decreased left ventricular ejection fraction, estimated at 15–20% and serum troponin peaked at 0.2 ng/dL, baseline platelet count was 203 × 10 3 /µL. He underwent a drug-eluting stent placement to the right coronary artery with excellent angiographic results. He received 3000 units of unfractionated heparin and 180 mg of ticagrelor during the procedure. About 6 h after the procedure, he had coffee ground emesis. A complete blood count revealed a platelet count of 2 × 10 3 and 0 × 10 3 /µL on repeat testing. Peripheral smear did not show any evidence of platelet clumping and schistocytes, serum haptoglobin and lactate dehydrogenase were normal. Ticagrelor and heparin were discontinued, while the aspirin was continued. Five units of platelet were transfused. The platelet count improved to 200 × 10 3 /µL. Since his CHADS2 VASC score was 3, he was discharged on apixaban and clopidogrel in addition to other medication. No thrombocytopenia was seen on outpatient follow-up. Discussion: The common side effects of ticagrelor include bleeding, dyspnoea, gynaecomastia, and rarely thrombotic thrombocytopenic purpura. Although extremely rare, absolute or profound thrombocytopenia can occur with ticagrelor, hours after administration and should be considered when other potential causes of thrombocytopenia have been ruled out.